Surveying the locally protected tree line of Gödöllő - Almási, Barnabás; Demeter, András; Hollósi, Aranka; Major, Borbála; Marton, Krisztina; Merza, Péter; Molnár, Levente; Nagy, Enikő; Piszker, Zoltán; Poller, Emese Fanni; Sarlós, Dávid; Ursu, Dorottya; et al. (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
The sycamore tree line of Gödöllő is considered as a protected natural value of local importance. There were 2012 locally protected nature conservation values and areas in 2013. These values and areas fulfill an important role in the network of Hungarian nature conservation areas. The general characteristic of these nature conservation values and areas of local importance is that we lack relevant information about them. This is why we thought that it would be useful to survey the line of sycamore trees on the Isaszeg Street of Gödöllő. During the survey we measured the perimeter and diameter of the trees and the distance between the trees at the height of the human chest. The perimeter of the tree varied between 152 and 368.3 cm while diameter varied between 48.4 and 117.3 cm. The distance between the trees were between 590 and 1450 cm.